American Spy - Wilkinson, Lauren (London Little Brown Book Group, 2019)
Marie Mitchell, a Cold War FBI intelligence officer, joins an undercover task force to undermine Thomas Sankara, the revolutionary Communist president of Burkina Faso, who she secretly admires and comes to love, in a novel inspired by true events. It's 1986, the heart of the Cold War, and Marie Mitchell is an intelligence officer with the FBI. She's brilliant, but she's also a young black woman working in an old boys' club. Her career has stalled out, she's overlooked for every high-profile squad, and her days are filled with monotonous paperwork. So when she's given the opportunity to join a shadowy task force aimed at undermining Thomas Sankara, the charismatic revolutionary president of Burkina Faso whose Communist ideology has made him a target for American intervention, she says yes. Yes, even though she secretly admires the work Sankara is doing for his country. Yes, even though she is still grieving the mysterious death of her sister, whose example led Marie to this career path in the first place. Yes, even though a furious part of her suspects she's being offered the job because of her appearance and not her talent. In the year that follows, Marie will observe Sankara, seduce him, and ultimately have a hand in the coup that will bring him down. But doing so will change everything she believes about what it means to be a spy, a lover, a sister, and a good American.
Keywords: Burkina Faso -- Sankara, Thomas -- African American women